1992
DOI: 10.1159/000236114
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization with Polyvalent Bacterial Lysate and Infection with <i>Streptococcus</i> <i>pneumoniae</i>: Influence on Interferon-Gamma and PMN Elastase Concentrations in Murine Bronchoalveolar Lavage Fluid

Abstract: We recently demonstrated that oral immunization with a polyvalent bacterial lysate (Paspat oral®) significantly reduces mortality rates in mice, infected with Streptococcus pneumoniae or influenza A virus. In this study it is demonstrated that oral immunization with the same bacterial lysate reduces the intrapulmonary inflammatory reaction to infection with S. pneumoniae, assessed by measurement of PMN elastase in bronchoalveolar lavage fluid. Furthermore, it is demonstrated that oral immunization with Paspat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our previous studies demonstrated enhanced peripheral polymorphonuclear leukocyte functions after oral application of bacterial antigens, as reflected by a significantly increased oxidative burst activity (10). Van Daal et al reported a reduction of intrapulmonary inflammatory reactions to infection with Streptococcus pneumoniae and an enhancement of pulmonary defense mechanisms mediated by increased gamma interferon production (32). Furthermore, we demonstrated that the orally applied bacterial lysate appreciably enhanced the rates of migration of intestinal lamina propria lymphocytes and Peyer's patch lymphocytes to the lungs when injected intravenously into untreated syngeneic recipients (28).…”
supporting
confidence: 57%
“…Our previous studies demonstrated enhanced peripheral polymorphonuclear leukocyte functions after oral application of bacterial antigens, as reflected by a significantly increased oxidative burst activity (10). Van Daal et al reported a reduction of intrapulmonary inflammatory reactions to infection with Streptococcus pneumoniae and an enhancement of pulmonary defense mechanisms mediated by increased gamma interferon production (32). Furthermore, we demonstrated that the orally applied bacterial lysate appreciably enhanced the rates of migration of intestinal lamina propria lymphocytes and Peyer's patch lymphocytes to the lungs when injected intravenously into untreated syngeneic recipients (28).…”
supporting
confidence: 57%
“…It has also been documented that the overexpressed intrapulmonary response to Streptococcus pneumoniae infection was reduced in animals orally immunized with the LW 50020 bacterial lysate, mainly by suppression of exaggerated PMN--elastase synthesis [17]. Simultaneously, enhancement of neutrophils, alveolar macrophages and peripheral blood cell phagocytic activity [27] as well as intensification of their oxidative capacity were observed as well [16,28].…”
Section: Lw 50020 (Luivac)mentioning
confidence: 97%
“…LW 50020 has been demonstrated to considerably stimulate lymphocytes proliferation as well as T cell activity in the mesenteric lymph nodes model [15,16]. Accordingly, up-regulated local production of IL-2 and IFN-g was observed in the mesenteric lymph nodes and BALf from experimental animals [15][16][17], while IL-5 and IL-6 secretion was enhanced in cultured animal pulmonary lymphocytes [18]. In healthy volunteers treated with LW 50020, up-regulation of T lymphocytes proliferative activity was noted, as well as increased relative numbers of CD4, CD8 and memory cells (CD45RO + ) in bronchial lamina propria.…”
Section: Lw 50020 (Luivac)mentioning
confidence: 99%
“…They are absorbed in the intestine generating the immune responses within mucosal tissues that extend to other organs including, lungs. 134,135 Bacterial immunomodulators are commercially available as OM-85 BV (Broncho-Vaxom), LW 50020 (Luivac), ISMIGEN, and Ribosomal extract (Ribomunyl); they consist of bacterial cells killed and subjected to mechanical, chemical, or enzymatic lysis or of isolated bacterial organelles. Usually, they are mixtures of several bacterial species most frequently responsible for respiratory tract infections, including Staphylococcus aureus, Streptococcus pyogenes, S. viridans, S. mitis, S. pneumoniae, Klebsiella pneumoniae, K. ozaenae, Moraxella catarrhalis, Haemophilus influenzae, and Diplococcus pneumoniae.…”
Section: Immunomodulators Towards Personalized Tb Treatmentmentioning
confidence: 99%